2004
DOI: 10.1007/s00775-004-0616-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging visualization of targeted cells by the internalization of supramolecular adducts formed between avidin and biotinylated Gd3+ chelates

Abstract: The high binding affinity between avidin and biotin has been exploited to develop a procedure for magnetic resonance imaging (MRI) visualization of target cells. SHIN3 and PANC1 tumor cell lines have been used as target cells because they possess on their membranes galactosyl receptors able to bind avidin molecules. Avidin-Gd chelate adducts have been built by using two Gd complexes containing one (Gd-I) and two (Gd-II) biotin residues, respectively. The relaxivities of such supramolecular adducts are signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Gd 3+ complexes have received most attention as contrast agents for MRI applications due to their large magnetic moment and a suitable long electronic relaxation time. However, there is no natural human biochemistry for Gd 3+ that can be exploited when designing its contrast agents derivates (3)(4)(5)(6). On the other hand, agents based on Mn 2+ , Fe 3+ , and Cu 2+ ions are attractive alternatives (7)(8)(9) because these metals are already present in tissues and there is extensive information available about their human biochemistry, including transport, storage, compartmentalization and excretion mechanisms.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gd 3+ complexes have received most attention as contrast agents for MRI applications due to their large magnetic moment and a suitable long electronic relaxation time. However, there is no natural human biochemistry for Gd 3+ that can be exploited when designing its contrast agents derivates (3)(4)(5)(6). On the other hand, agents based on Mn 2+ , Fe 3+ , and Cu 2+ ions are attractive alternatives (7)(8)(9) because these metals are already present in tissues and there is extensive information available about their human biochemistry, including transport, storage, compartmentalization and excretion mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…The complex [(tacn) 6 Fe 8 (µ 3 -O) 2 (µ 2 -OH) 12 ]Br 8 · 9H 2 O, where tacn = 1,4,6-triazacyclononane, and hereafter referred to as Fe 8 , was chosen by us in order to study its potential as contrast agent (13). Due to the size of Fe 8 molecules, the distribution and residence time in the tissues should be different and produce complementary information to that given by Gd-based chelates and iron oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent in vitro studies showed that biotin-BSA-GdDTPA was effectively internalized by fibroblasts using caveolae mediated uptake, which could be suppressed by treatment with nystatin(9), (11). Upon internalization, the material is sequestered within small intracellular vacuoles leading to suppressed MRI relaxivity, which is regained only after the material is redistributed in the cells with cell division (12) (9). The contrast material did not extravasate into the interstitial space within the tumor nodules (9).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Moreover, in the case of well-spaced bisbiotinylated compounds the formation of long chain polymers is, in part, hampered by the occurrence of intramolecular linkages, as previously shown in the case of biotin-DTPA dimers. [10] Therefore, molecules with three biotin moieties have to be designed to allow the formation of polymeric chains. Furthermore, we have to take into account not only that two of the three biotin moieties in tribiotinylated compounds would bind to the same protein molecule, but also the space needed for the insertion of three Gd III -DOTAMA complexes.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Gd-DTPA-like complexes (DPTA = diethylenetriamine pentaacetic acid) containing one and two biotin residues were synthesized and their adducts with avidin were tested in vitro. Evidence for the occurrence of multilayered adducts in which the bisbiotinylated Gd III complex bridged adjacent avidin molecules was obtained.…”
mentioning
confidence: 99%